THE ROLE OF CUSTOMER NETWORKING CAPABILITY EFFECTIVENESS IN ENHANCING THE SALESPEOPLE’S PERFORMANCE IN SMALL AND MEDIUM ENTERPRISES - Udayana, Ida Bagus Nyoman; Farida, Naili (UI Scholars Hub, 2021)
Research Aims: This research examines the research gap between adaptive selling and the salespeople’s performance. There is an inconsistency of research results among marketing researchers. This study extends the previous marketing literature to customer network-based marketing. Design/Methodology/approach: The research data were collected from 300 salesperson in the field of small and medium enterprises. The data analysis used a structural equation model and Sobel tests. The findings of the research: Research findings show that the effectiveness of customer networking capability functions as an intervention between adaptive selling and salespeople’s performance. Adaptive selling, interaction quality, and perceived interpersonal skills have a significant positive effect on the effectiveness of customer networking capability and salespeople’s performance. Theoretical Contribution/Originality: The current study develops networking theory and tries to contribute to the literature, which serves as a step towards broadening the concept of customer networking. Practitioner/Policy Implication: Managers can also build a network of customers who can communicate well. This communication supports long-term relationships and mutual benefits between customers and the company. To sustain long-term relationships, a company monitors customers through the network of effective communication. Research limitation/Implication: As this research was undertaken in Indonesia, the collected data merely represents the country’s sales and marketing situations. The findings may not apply in all countries. Conducting the same type of research in other Asian countries can test the accuracy of the model empirically.